An image fusion technique using Slantlet transform and phase congruency for MRI/CT. (1st January 2013) - Arathi, T.; Parameswaran, Latha
Image fusion aims at maximally making available, the information from two or more input images of the same scene into a single composite image. Medical images are acquired using different modalities, which include MRI, CT scan, PET and SPECT images. Fusing them makes available the information from multiple images into a single composite image, aiding doctors in easier diagnosis. Most existing fusion techniques give more importance to the quality of the fused image, than the computational complexity. In this research, a new image fusion technique addressing computational complexity has been proposed, for combining MRI and CT images. The method has been found to be computationally efficient, in terms of the number of transform domain coefficients participating in the fusion process, without any compromise in the visual quality of the fused image. Experimental results exhibit the efficacy of this proposed technique, both in terms of computational cost and image quality.